2017
DOI: 10.1182/bloodadvances.2017009514
|View full text |Cite
|
Sign up to set email alerts
|

A clinical audit of thrombophilia testing in pediatric patients with acute thromboembolic events: impact on management

Abstract: Key Points• Thrombophilia testing does not affect clinical management in the acute setting after a TEE in children and should be avoided.• Potential harms of thrombophilia testing include unnecessary blood draws in children and an estimated cost of $82 000.Routine testing for inherited and acquired thrombophilia defects is frequently performed in pediatric patients with thromboembolic events (TEEs). No consensus guidelines exist regarding the timing of testing or the type of patients to be tested. The primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The percentage of patients with inappropriate indications for testing in this study are in agreement with several recent similar studies. Shen et al reporting appropriate indications in 34% of patients, in which appropriate testing was also defined as an unprovoked thrombosis or ≥ 3 pregnancy losses [9]. The authors established local guidelines to prevent testing during the acute thrombotic event or while the patient is on anticoagulation, resulting in an 84% reduction in ordered tests after 22 months and an estimated savings of over $100,000 per month.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of patients with inappropriate indications for testing in this study are in agreement with several recent similar studies. Shen et al reporting appropriate indications in 34% of patients, in which appropriate testing was also defined as an unprovoked thrombosis or ≥ 3 pregnancy losses [9]. The authors established local guidelines to prevent testing during the acute thrombotic event or while the patient is on anticoagulation, resulting in an 84% reduction in ordered tests after 22 months and an estimated savings of over $100,000 per month.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, testing for thrombophilia is costly, with panels ranging from $1,100 and $2,400, and annual Medicare spending between $300-$672 million in the USA on thrombophilia testing [7,8]. Institutional studies have reported annual costs of $62,000 to over $1 million for thrombophilia testing [9,10]. Shen et al reported that consultation with transfusion medicine service prior to ordering thrombophilia tests saved $104,400 per month and reduced panels ordered by 92% [10].…”
Section: Introductionmentioning
confidence: 99%
“…In general, thrombophilia testing has not impacted management and results in iatrogenic blood loss and cost. 23 AT activity testing, before initiation of anticoagulation, is most useful to determine whether replacement is indicated to achieve heparin efficacy. However, given the critical timing and potentially fatal outcomes, we recommend empiric administration of AT replacement at time of heparin initiation since neonates are expected to have low levels of AT.…”
Section: Thrombophilia Evaluationmentioning
confidence: 99%
“…The developmental stage of the hemostatic system in children, physiologically lower levels of coagulant and anticoagulant proteins, and other confounding factors, such as concomitant use of drug, infection, or inflammation, should be addressed [ 68 - 70 ]. Generally, the tests for thrombophilia do not change decisions about the initiation and duration of acute management, except for specific patients with purpura fulminans complicating severe protein C or S deficiency or cases with VKA-induced skin necrosis [ 71 - 73 ].…”
Section: Treatment Of Venous Thromboembolismmentioning
confidence: 99%